PHOSPHATIDYLETHANOLAMINE-BINDING PROTEINS the conductors of dual reproduction in plants with vegetative storage organs - Khosa, Jiffinvir (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology.